STRATEGI KOMUNIKASI KEPEMIMPINAN DALAM MENGATASI KRISIS DI J&T EXPRESS CABANG LIMO KOTA DEPOK - Nafa Azzahra, Najwa; Mutiah, Tuty; Saputra Dewa, Faris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Operational crises in logistics service companies are among the major challenges that can disrupt the distribution process and affect customer trust in service quality. Therefore, effective leadership communication strategies are essential to ensure that crisis management is carried out efficiently and appropriately. This study aims to analyze the leadership communication strategy in managing operational crises at J&T Express Limo Branch, Depok City, using the perspective of the Situational Crisis Communication Theory (SCCT). This research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observations, and documentation involving the Supervisor (SPV) and the Operational Administrator as the research informants. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation techniques. The findings indicate that operational crises are caused by both internal and external factors, including increased shipment volume, operational errors, system disruptions, adverse weather conditions, and traffic congestion. To address these challenges, the company implements leadership communication strategies that emphasize prompt responses, transparency, consistent communication, and accountability through internal coordination and effective communication with customers. In addition, the company conducts evaluations of the causes of crises and improves operational procedures to enhance the effectiveness of crisis management. The implementation of these communication strategies contributes to maintaining and restoring customer trust in the services provided by J&T Express Limo Branch, Depok City.